Effect of Spent Mushroom Compost of Pleurotus eous Strain P-31 on Growth Performance and Nodulation ff Cowpea (Vigna u nguiculata Walp.) - Wiafe-Kwagyan Michael; Odamtten George Tawia; Kortei Nii Korley (Tropical Life Sciences Research, 2022)
This study investigated the influence of spent mushroom compost (SMC) of Pleurotus eous strain P-31 on the growth, development and soil rhizobial population associated with nodulation of cowpea (Vigna unguiculata Walp.) black-eye variety, under greenhouse conditions at 28 ± 2°C for 12 weeks. Sandy loam soil was combined with different percentages of SMC to obtain the following combinations (0%, 5%, 10%, 15%, 20%, 25%, 30%, 100%). Lower concentrations, SMC (5%–25%) promoted plant height, number of leaves, total leaf area, total chlorophyll, chlorophyll a and b as well as dry matter accumulation of shoot and roots after 12 weeks at 28°C–32°C. Soil: SMC concentrations beyond 30% SMC variably depressed the various developmental criteria used in assessing growth. The trend obtained in the assessed parameter were statistically significant (p ? 0.05) in decreasing order: 5% SMC < 10% SMC < 15% SMC, < 20% SMC, < 25% SMC, < 30% SMC, < 100% SMC. The cowpea plant efficiently assimilated nitrogen (N2) from the soil: compost. Nodule formation by cowpea was commensurate with increasing percentage of spent compost was highest in 5% SMC (89/plant) and declined with increasing proportion of SMC: soil mixture up to 25% but nodulation of cowpea plant was completely depressed in the absence of soil (100% SMC) pots. The Nodule Index data showed that the best nodule size and weight were formed by cowpea growing in medium containing 5% SMC (18) and 10% SMC (12) and thereafter declined. The nodules were red to pinkish in colour epitomising leghaemoglobin which could initiate nodulation and N2 fixation in soil. This study has shown that 5% SMC–20% SMC could provide favourable conditions in soil as a biofertiliser to improve the growth, development and nodulation of cowpea.